Analysis of Lightning Disruption Reduction in HVAD Tower 70 kV Parallel Inductance Grounding using NA2XSY Cable in West Java - Siswanto, Agus; Mucharomah, Nurul Maghfiroh; Ashad, Bayu Adrian; Rahman, Yuli Asmi (Politeknik Negeri Ujung Pandang, 2020)
The Sumadra - Pameungpeuk region has an uneven geographical location because it is traversed by mountains and beaches and has a high level of ISO Keraunic which causes many lightning strikes to occur in this region. The disturbance caused by lightning strikes is very worrying because it can disrupt the stability of electric power in West Java, Integrated Service Unit (ISU) Cirebon region in particular and can harm consumers as users of electricity. To minimize the disruption caused by lightning strikes in this study using the parallel mounting inductance method using NA2XSY cable. This study aims if there is a lightning strike on the GSW wire it can be immediately properly grounded. NA2XSY cable was chosen as direct grounding because the inductance value on the cable is smaller than the inductance value on the tower so that when NA2XSY cable is paralleled with the body tower it produces a low parallel inductance value so that it is expected to minimize the occurrence of back flashover due to the induction voltage resulting in the flash isolator. The results showed the lowest tower resistance value in the Sumadra-Pameungpeuk region of 0.21 ohms is located at tower number 77 and the highest resistance is 4.3 ohms at tower numbers 49 feet A and D, this meets PLN's standard of <5 ohms. Parallel inductance installation succeeded in reducing the disturbances caused by lightning, namely, in January-July 2018 the disruption occurred 4 times and in January - July 2019 became 2 times the disturbance.